The construction of gamer identity in narratives about video game playing and formal education learning experiences - Jingyang Ai; Beth Cross; Carole Bignell (Association for Learning Technology, 2023)
This study investigates how video game play influences gamers' formal education through perceptions of their 'gamer' and 'learner' identities. Based on identity foundation in symbolic interactionism, we take gamer and learner identities as meaning structures with both dynamic and stable dimensions. The basis of this gamer identity perspective is identity has a crucial role in investigating learning. Applying a life history approach, we interviewed 10 participants in one-to-one interviews, with three interviews for each participant. Applying the narrative portrait, we analysed participant data. We found that gamer identity construction from video game playing, as a vital meaning structure, has four main aspects, namely in-game identification, social community expansion, restorative effect and meaning recognition, providing gamers with expansive ways to build learner and personal identity as that can benefit their formal education.